Questionnaire Data.xlsx - WENJING GUO (20688356) (2025)
The participants in this study were graphic design students from a university. Researchers organized the students to test the ChtAR APP prototype and complete a user engagement questionnaire. Finally, descriptive statistical analysis and multiple linear regression analysis of 112 valid questionnaires showed that the ChtAR design pattern significantly enhances user engagement.